PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 27 PADANG - HANDAYANI, MATRI; Rismen, Sefna; Husna, Husna (Pendidikan Matematika, 2014)
Â ABSTRACTÂ Background of this research is studentâs grade VII SMPN 27 Padang comprehension of mathematical concepts still low. In that case endence when studentâs are less active in the learning process. The purpose of this research is to know how studentâs activity in the learning process and to know what is studentâs comprehension of mathematical concept at grade VII SMPN 27 Padang by using the power of two strategy better than convensional model. The population is studentâs at grade VII SMPN 27 Padang. To take sample in this research is randomly so that, the researchergotten grade VII.4 as experiment class and VII.3 as control classÂ  the instrumentation is used in this research isÂ  comprehension test of mathematical concept and sheet activity. Type of test is used type essay with realibilitas test is . Tecnique of analysis data is t-test one side by using software minitab therefore, the final analysis with a = 0,05 be obtained P-value = 0,041, because P-value minus for a, so hipothesis is accepted in this research. So that it can be concluded that studentâs comprehension of mathematical concept is treated by using the power of two strategy better than studentâs comprehension of mathematical concepts is treated by using convensional model at grade VII SMPN 27 Padang.